In Vitro Anti-Tubulin Activity on MCF10A Cell Line and In Silico Rigid/Semiflexible-Residues Docking, of Two Lignans from Bursera Fagaroides var. Fagaroides - Rodríguez-López, Verónica; Millán-Pacheco, César; González-Christen, Judith; Anaya-Ruíz, Maricruz; Peña-Morán, Omar Aristeo (Molecules (Basel, Switzerland), 2021)
Podophyllotoxins are natural lignans with known cytotoxic activity on several cell lines. The structural basis for their actions is mainly by the aryltetralin-lignan skeleton. Authors have proposed a cytotoxic mechanism of podophyllotoxins through the topoisomerase-II inhibition activity; however, several studies have also suggested that podophyllotoxins can inhibit the microtubules polymerization. In this work, the two possible mechanisms of action of two previously isolated compounds from the stem bark of Bursera fagaroides var. fagaroides: acetylpodophyllotoxin (1) and 5’-desmethoxydeoxypodophyllotoxin (2), was analyzed. An in vitro anti-tubulin epifluorescence on the MCF10A cell line and enzymatic topoisomerase II assays were performed. The binding affinities of compounds 1 and 2 in the colchicine binding site of tubulin by using rigid- and semiflexible-residues were calculated and compared using in silico docking methods. The two lignans were active by the in vitro anti-tubulin assay but could not inhibit TOP2 activity. In the in silico analysis, the binding modes of compounds into both rigid- and semiflexible-residues of tubulin were predicted, and only for the semiflexible docking method, a linear correlation between the dissociation constant and IC50 previously reported was found. Our results suggest that a simple semiflexible-residues modification in docking methods could provide an in vitro correlation when analyzing very structurally similar compounds.